Vino nuevo en odres viejos – El Partido Comunista de la Argentina ante la revolución verde de los años ’60 y ‘70 - Guido Lissandrello (Nuevo mundo - Mundos Nuevos, 2020)
In this article, we intend to reconstruct the analysis and positioning of the Communist Party against the Argentine agrarian question, in the 60s and 70s, marked by the great productive transformations. To do this, we examine the theoretical articles of his intellectual magazine, Nueva Era, in which the economic and agricultural specialists of the party wrote. We maintain, as a hypothesis, that the PC did not abandon the study of agrarian reality and, on the contrary, showed to be especially attentive to recent transformations, realizing it in the theoretical materials that it developed. At the same time, we propose that, contradictorily, the perception of these changes did not lead him to modify his characterization of the countryside, marked by the large estates, peasant ruin and productive stagnation. In this way, we believe to contribute to a more general historiographic problem, that which refers to the complex and contradictory ways in which the left tried to study reality and adapt it to own political conceptions that were the result of preconceived ideas.